2020
DOI: 10.26466/opus.631378
|View full text |Cite
|
Sign up to set email alerts
|

Okul Öncesi Öğretmenlerinin Fen Eğitiminin İçeriği ve Standartlarına İlişkin Görüşlerinin İncelenmesi

Abstract: Bu çalışma ilk yazarın yüksek lisans tezinden üretilmiştir. OPUS *Bu çalışma ilk yazarın yüksek lisans tezinden üretilmiştir. OPUS AbstractIn this study, teacher opinions on the content of science education at pre-school educational institutions are aimed to be analyzed. In addition to this, the current situation with regard to the applications of science education at pre-school level has been attempted to be identified. Target population of the study consisted of 150 teachers who worked with 36 to 72-month ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 27 publications
(20 reference statements)
0
5
0
5
Order By: Relevance
“…Most of the teachers stated that mathematics is all/indispensable/everything in life, number, logical thinking, and reasoning skills. Dağlı and Dağlıoğlu (2018), in their study to determine children's perceptions towards mathematics, concluded that children mostly recognised numbers, geometry and grouping materials; they did not recognise the materials that included matching, measurement, part-whole relationship and most of the children did not use these materials. Dağlı and Dağlıoğlu (2018) found that children associated mathematics with numbers the most, and de ned it as "studying".…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most of the teachers stated that mathematics is all/indispensable/everything in life, number, logical thinking, and reasoning skills. Dağlı and Dağlıoğlu (2018), in their study to determine children's perceptions towards mathematics, concluded that children mostly recognised numbers, geometry and grouping materials; they did not recognise the materials that included matching, measurement, part-whole relationship and most of the children did not use these materials. Dağlı and Dağlıoğlu (2018) found that children associated mathematics with numbers the most, and de ned it as "studying".…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Teachers' mathematics anxiety affects children's mathematics anxiety or mathematics achievement (Beilock et al, 2010). They stated that the experiences offered to children and conversations with children are effective in children's views on mathematics, that their perceptions of mathematics are mostly gained from social experiences, and that as a result, children have negative perceptions of mathematics from a very young age (Dağlı and Dağlıoğlu, 2018). Considering that children do not yet have mathematics anxiety at an early age, it is necessary to emphasise the importance of the preschool period and the importance of educators' thoughts and perceptions in order to prevent children from having mathematics anxiety in their future lives.…”
Section: Children's and Teachers' Perceptions Of Mathematics In Early...mentioning
confidence: 99%
See 1 more Smart Citation
“…Kazanımların hatırlama, anlama, uygulama ve analiz basamaklarına dengeli olarak dağıldığı ve bu 4 basamakta kullanılan kazanımların toplam kazanımların %91,7' sini oluşturduğu görülmektedir. Yapılan çalışmalar öğretmenlerin fen etkinliklerinde en fazla deneye yer verdiklerini ve aynı zamanda anlatım tekniğini çok fazla kullandığını ortaya koymaktadır (Dağlı & Dağlıoğlu, 2020;Ültay, Ültay & Çilingir, 2018). Okul öncesi sınıflarına yönelik hazırlanan hazır planların incelenmesi sonucunda da en fazla deney yer verildiği bulunmuştur (Alabay & Yağan Güder, 2015).…”
Section: Bulgular Veunclassified
“…Gözlem ve deneyime dayanan, çocuklara gerçek yaşam deneyimleri sunan, onların bütün duyularına hitap eden ve farklı öğrenme yaklaşımları ile desteklenen proje yaklaşımları ile çocukların kavramsal gelişimlerine önemli katkılar sağlamaktadır (Yalçın ve Tekbıyık, 2013). Alan yazın incelendiğinde okul öncesi öğretmenlerinin fen eğitimine yönelik tutumları, fen etkinlikleri hakkındaki görüşleri, fen etkinliklerinde kullanılan yöntemler, öğretmenlerin fen konularında yapmış oldukları uygulamalar ve fen eğitiminin içeriği konusunda öğretmen görüşlerinin incelendiği görülmektedir (Babaroğlu ve Okur Metwalley, 2018;Dağlı ve Dağlıoğlu, 2020;Elmas ve Kanmaz, 2015;Karamustafaoğlu ve Kandaz, 2006;Okur Akçay, 2014;Sağlam ve Aral, 2015;Ültay, Ültay ve Çilingir, 2018). Bu çalışma, okul öncesi öğretmenlerinin hem yeterlikleri hem de fen eğitiminde kullanılan yöntem ve tekniklere yönelik görüşlerini ele alan bir araştırma sağlaması açısından önem taşımaktadır.…”
Section: Introductionunclassified